Referral letters to the psychiatrist in Nigeria: is communication adequate? (2016)
Objective: Over half of patients with psychiatric disorders are first seen by primary care physicians before referral to the psychiatrist. An efficient referral system is, therefore, important to offering quality care to such patients. Communication between physicians is often sub-optimal and referral letters to specialists sometimes provide inadequate information. The current study’s aim was to observe the prevalence of deficiencies in the referral letters to a department of psychiatry in a Nigerian teaching hospital. Methods: All referral letters to the Department of Psychiatry, University College Hospital Ibadan, Nigeria over a three- year period from January 1, 2010, to December 31, 2012, were retrieved and assessed for quality using the Consultation and Referral Request Letter Assessment Tool. Result: A majority (>80%) of the referral letters had no information on the current medication list, relevant psychosocial history, outline of management to date, results of investigations to date, and known allergies. Conclusion: Deficits in communication or information transfer through referral letters to the psychiatrist are common. Interventions such as the use of standardized formats for such letters may facilitate more efficient communication.